Belis: Sebuah Tradisi Perkawinan Suku Dawan - Fredirikus Nono (Jurnal Teologi dan Pelayanan Kerusso, 2022)
Belis is a tradition that has noble values ​​and a form of respect for women. The purpose of this study is to describe the Belis tradition and the importance of Belis in the traditional marriage of the Dawan-Timor tribe. In addition, this study also aims to link and compare the Belis culture with the marriage law of the Catholic church which is regulated in the Code of Canon Law of the Catholic Church, especially with regard to the Marriage Agreement. The results showed that Belis is a tradition in the traditional marriage of the Dawan tribe. This Belis tradition has been abandoned and adopted by the Dawan community on the island of Timor. In the traditional marriage of the Dawan people, Belis always has a very important and main role. It is said that when we talk about marriage, we are talking about belis. In this study, it was also found that Belis became one of the problems and obstacles for the Dawan community in terms of marriage. Belis seems to be considered more important and is used as the main condition in marriage so that it seems to override the main requirements of marriage in the marriage law of the Catholic church. The research method used is a comparative study with a descriptive approach. Methods of data collection using a literature review. Abstrak Indonesia Belis merupakan tradisi yang memiliki nilai-nilai luhur dan bentuk penghargaan terhadap perempuan. Tujuan penelitian ini ialah untuk mendeskripsikan tentang tradisi Belis dan pentingnya Belis dalam perkawinan adat suku Dawan-Timor. Selian itu, penelitian ini juga bertujuan untuk mengaitkan dan membandingkan budaya Belis tersebut dengan hukum perkawinan gereja Katolik yang diatur dalam Kitab Hukum Kanonik Gereja Katolik, khususnya yang berkaitan dengan Kesepakatan Nikah. Hasil penelitian menunjukkan bahwa Belis merupakan tradisi dalam perkawinan adat suku Dawan. Tradisi Belis ini telah ditinggalkan dan diadopsi oleh masyarakat Dawan di pulau Timor. Dalam perkawinan adat masyarakat Dawan, Belis selalu mempunyai peran yang sangat penting dan utama. Dikatakan bahwa jika berbicara soal perkawinan berarti berbicara soal Belis. Dalam penelitian ini ditemukan juga bahwa Belis menjadi salah satu masalah dan hambatan bagi masyarakat Dawan dalam hal perkwainan. Belis terkesan dianggap lebih penting dan dijadikan sebagai syarat utama dalam perkawinan sehingga terkesan mengesampingkan syarat utama perkawinan dalam hukum perkawinan gereja Katolik. Metode penelitian yang digunakan adalah studi komparatif dengan pendekatan deskriptif. Metode pengumpulan data menggunakan tinjauan pustaka.